CT and MRI characterization of presumed persistent ossiculum terminale in dogs. Issue 1 (5th September 2022) - Bourbos, Alexandros; Rowan, Conor; Cinti, Filippo; Pisani, Guido; Piola, Valentina
Abstract: Anecdotally, during the review of CT and MRI studies of canine patients including the cranial cervical spine, authors have identified a small osseous structure between the atlas (C1) and axis (C2) with no relevant clinical signs. This structure appeared comparable to a "persistent ossiculum terminale" in humans. The aim of this retrospective, multi‐center, case series study was to describe the CT and MRI features of presumed persistent ossiculum terminale in a group of dogs presented with unrelated medical conditions.  Two databases (the imaging database of the teleradiology service VetCT Specialists and the clinical database of the University of Vienna) were scrutinized by different approaches. Medical records of dogs that underwent imaging investigation (CT and/or MRI) that included the atlanto‐axial junction were reviewed. Data collected included signalment, sex, breed, age, presenting symptoms, and final diagnosis. Eighteen dogs met the inclusion criteria. Mean age was 85 months (6–166) and breed variation was present. A total of 20 imaging studies were evaluated: CT was performed in 17 dogs; MRI in three dogs; two dogs had both MRI and CT performed. In all cases the presence of at least one small osseous body on the cranial aspect of the odontoid process compatible with a persistent ossiculum terminale was identified as a possible incidental finding without any overt clinical implications. Findings indicated that a small osseous body on the cranial aspect of the odontoid process (presumed persistent ossiculum terminale) in CT and MRI studies may be present in dogs with no clinical signs of neurologic disease.